Short-term and long-term case-fatality rates for myocardial infarction and ischaemic stroke by socioeconomic position and sex: a population-based cohort study in Sweden, 1990–1994 and 2005–2009 - Alexander Ploner; Pär Sparén; Ninoa Malki; Sara Hägg; Sanna Tiikkaja; Ilona Koupil (BMJ Open)
Objective Case-fatality rates (CFRs) for myocardial infarction (MI) and ischaemic stroke (IS) have decreased over time due to better prevention, medication and hospital care. It is unclear whether these improvements have been equally distributed according to socioeconomic position (SEP) and sex. The aim of this study is to analyse differences in short-term and long-term CFR for MI and IS by SEP and sex between the periods 1990–1994 to 2005–2009 for the entire Swedish population.Design Population-based cohort study based on Swedish national registers.Methods We used logistic regression and flexible parametric models to estimate short-term CFR (death before reaching the hospital or on the disease event day) and long-term CFR (1 year case-fatality conditional on surviving short-term) across five distinct SEP groups, as well as CFR differences (CFRDs) between SEP groups for both MI and IS from 1990–1994 to 2005–2009.Results Overall short-term CFR for both MI and IS decreased between study periods. For MI, differences in short-term and long-term CFR between the least and most favourable SEP group were generally stable, except in long-term CFR among women; intermediate SEP groups mostly managed to catch up with the most favourable SEP group. For IS, short-term CFRD generally decreased compared with the most favourable group; but long-term CFRD were mostly stable, except for an increase for older subjects.Conclusion Despite a general decline in CFR for MI and IS across all SEP groups and both sexes as well as some reductions in CFRD, we found persistent and even increasing CFRD among the least advantaged SEP groups, older patients and women. We speculate that targeted prevention rather than treatment strategies have the potential to reduce these inequalities.